KONTRIBUSI CARA BELAJAR MATEMATIKA TERHADAP HASIL BELAJAR MATA KULIAH ANALISIS MATEMATIKA MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN JURUSAN TEKNIK SIPIL FT-UNP - 2022-2027, Akmal Hadi (Universitas Negeri Padang, 2018)
Abstract— This research begins from the still many students who get low learning result in Mathematics Analysis Course. This research aims to determine the contribution of how to learn mathematics learning outcomes Mathematics Analysis courses and find out how much the contribution of mathematics learning to the results of learning subjects Mathematics Analysis of students Studies Program Building Engineering Education Department of Civil Engineering FT-UNP. The type of this research is descriptive correlation. The sample of this research is 62 students of Engineering Engineering Education Study Program class of 2017. The instrument used is questionnaire to measure the variable of how to learn mathematics. Test questionnaire how to learn mathematics obtained 31 items valid statement with reliablitas 0,892. The results showed that there was a contribution of the way of learning mathematics to the learning result of Mathematics Analysis course of the students of the Faculty of Engineering FT-UNP. The result of correlation test is rcount 0,408> rtable 0,250 at significance level α 5%, in tcount test is 3,462> ttable 1,66980, and on determination coefficient test obtained KP value 16,64%. So it can be concluded that there is a contribution of the way of learning mathematics to the learning outcomes of Mathematics Analysis course of students of Building Engineering Education Program of Department of Civil Engineering FT-UNP of 16.64%.Keywords: How to Learn Mathematics, Learning Outcomes, Mathematical Analysis